Three-Phase Model of Visco-Elastic Incompressible Fluid Flow and Its Computational Implementation (Communications in Computational Physics, 2018)
Energetic Variational Approach is used to derive a novel thermodynamicallyconsistent three-phase model of a mixture of Newtonian and visco-elastic fluids.The model which automatically satisfies the energy dissipation law and is Galileaninvariant, consists of coupled Navier-Stokes and Cahn-Hilliard equations. ModifiedGeneral Navier Boundary Condition with fluid elasticity taken into account is also introducedfor using the model to study moving contact line problems. Energy stablenumerical scheme is developed to solve system of model equations efficiently. Convergenceof the numerical scheme is verified by simulating a droplet sliding on aninclined plane under gravity. The model can be applied for studying various biologicalor biophysical problems. Predictive abilities of the model are demonstrated bysimulating deformation of venous blood clots with different visco-elastic propertiesand experimentally observed internal structures under different biologically relevantshear blood flow conditions.
Keywords: Phase field method; Energetic Variational Approach; multi-phase flow; visco-elasticity; variable density; slip boundary condition; deformation of blood clot; thrombus.